Police Violence, Student Protests, and Educational Performance - González, Felipe; Prem, Mounu (The Review of Economics and Statistics, 2024)
Abstract We study the protest behavior of teenagers linked to a student killed by a stray bullet coming from a policeman in Chile. We use administrative data to follow the schoolmates of the victim and those living near the shooting on hundreds of protest and nonprotest days. We find that police violence causes lower protest participation in street rallies but more adherence to test boycotts. These effects appear among schoolmates of the victim and not among students living near the killing. Negative educational consequences suffered by the schoolmates combined with previous results suggest that psychological mechanisms are a plausible explanation.